Combinatorial strategies for cell transplantation in traumatic spinal cord injury - Jagrit, Vipin; Koffler, Jacob; Dulin, Jennifer N. (Frontiers in Neuroscience, 2024)
Spinal cord injury (SCI) substantially reduces the quality of life of affected individuals. Recovery of function is therefore a primary concern of the patient population and a primary goal for therapeutic interventions. Currently, even with growing numbers of clinical trials, there are still no effective treatments that can improve neurological outcomes after SCI. A large body of work has demonstrated that transplantation of neural stem/progenitor cells (NSPCs) can promote regeneration of the injured spinal cord by providing new neurons that can integrate into injured host neural circuitry. Despite these promising findings, the degree of functional recovery observed after NSPC transplantation remains modest. It is evident that treatment of such a complex injury cannot be addressed with a single therapeutic approach. In this mini-review, we discuss combinatorial strategies that can be used along with NSPC transplantation to promote spinal cord regeneration. We begin by introducing bioengineering and neuromodulatory approaches, and highlight promising work using these strategies in integration with NSPCs transplantation. The future of NSPC transplantation will likely include a multi-factorial approach, combining stem cells with biomaterials and/or neuromodulation as a promising treatment for SCI.